All‐Graphitic Multilaminate Mesoporous Membranes by Interlayer‐Confined Molecular Assembly. Issue 24 (19th May 2021) - Cai, Qingfu; Wang, Jing; Jiao, Yucong; Li, Tongtao; Xia, Yan; Li, Mingzhong; Yang, Yuchi; Wu, Guanhong; Zou, Jinxiang; Hu, Jianhua; Dong, Angang; Yang, Dong
Abstract: Layered mesostructured graphene, which combines the intrinsic advantages of planar graphene and mesoporous materials, has become interestingly important for energy storage and conversion applications. Here, an interlayer‐confined molecular assembly method is presented for constructing all‐graphitic multilaminate membranes (MMG⊂rGO), which are composed of monolayer mesoporous graphene (MMG) sandwiched between reduced graphene oxide (rGO) sheets. Hybrid assembly of iron‐oleate complexes and organically modified GO sheets enables the preferential assembly of iron‐oleate precursors at the interlayer space of densely stacked GO, driven by the like‐pair molecular van der Waals interactions. Confined pyrolysis of iron‐oleate complexes at GO interlayers leads to close‐packed, carbon‐coated Fe3 O4 nanocrystal arrays, which serve as intermediates to template the subsequent formation of MMG⊂rGO membranes. To demonstrate their application potentials, MMG⊂rGO membranes are exploited as dual‐functional interlayers to boost the performance of Li–S batteries by concurrently suppressing the shuttle of polysulfides and the growth of Li dendrites. This work showcases the capability of molecular‐based hybrid assembly for synthesizing multilayer mesostructured graphene with high packing density and its use in electrochemical energy applications. Abstract : An interlayer‐confined molecular assembly strategy is devised to construct the all‐graphitic multilaminate membranes (MMG⊂rGO) comprising monolayer mesoporous graphene sandwiched between reduced graphene oxide sheets. Thanks to their high surface area, uniform mesopores, and highly graphitic nature, MMG⊂rGO membranes can be used as dual‐functional interlayers to boost the performance of Li–S batteries.